Integrated geophysical and geochemical study for investigating the hydrocarbon potentiality of West Dakhla area, Western Desert, Egypt, as an extension of Libyan Kufra basin - GHONEIMI, Ashraf; GAWISH, Nashat S.; NABIH, Muhammad (Contributions to Geophysics and Geodesy, 2022)
The present study represents an integrated study using the potential field maps and well geochemical data of the West Dakhla area in the western central area of the Western Desert area, Egypt. The potential field data are represented by the airborne gravity and total magnetic maps acquired by the Nuclear Material Authority (NMA), Egypt, on behalf of Dana Petroleum Company. The geochemical data consist of geochemical analysis in Ammonite-1 well that were done for source rock evaluation. Different processing techniques on the gravity and magnetic maps are carried out for separating the regional and residual separation and filtering. Modelling and Euler deconvolution tools are utilized for proposing the depth to basement and constructing basement-depth maps to infer the basin configuration of the study area. Before acquiring the present geophysical data, the study area wasn't subjected to any exploration investigations. Therefore, these data and this study are considered as the first efforts carried out and submitted for publication in this area. In addition, a comparison of the present basin is done with matched basins in southern Libya, where this basin is expected to have similar geological features. The study indicates that the studied basin may be a part of a wider basin extending in Egypt and Libya. This basin is expected to have the thickness and features that are favourable for hydrocarbon habitat. The geochemical analysis shows TOC values ranging from poor to very good source rock potentiality.